Peran Humas dalam Perspektif Islam dalam Studi Kasus di Badan Pengawas Pemilu Provinsi Jawa Barat dalam Pelaksanaan Pemilu - Fazri Rahmat Syafitri; Bambang Saiful Ma'arif; Malki Ahmad Nasir (Bandung Conference Series: Islamic Broadcast Communication, 2024)
Abstract. This dissertation explores the field of public relations by analyzing its role from an Islamic perspective, with a specific focus on the Election Supervisory Board in West Java Province during election periods, the aim of this study is to comprehend how the role of public relations, as viewed through the lens of Islam, is applied within the context of election oversight, through a qualitative approach, this research gathers data through in-depth interviews and the analysis of relevant documents, the research findings reveal that the role of public relations, within the Islamic perspective, involves honest and transparent communication, aimed at fostering trust within the community. Public relations acts as a bridge between institutions and the public, prioritizing Islamic ethical values in information dissemination. In the context of the Election Supervisory Board in West Java Province, public relations plays a crucial role in ensuring fair and transparent election proceedings in accordance with Islamic principles. This study contributes to understanding how Islam can provide a conceptual framework for the role of public relations in the context of election oversight. Abstrak. Disertasi dalam humas dengan menganalisis peran Humas dalam perspektif Islam, dengan studi kasus di Badan Pengawas Pemilu Provinsi Jawa Barat selama pelaksanaan pemilu. Penelitian ini bertujuan untuk memahami bagaimana peran Humas dalam pandangan Islam diterapkan dalam konteks pengawasan pemilu. Melalui pendekatan kualitatif, penelitian ini mengumpulkan data melalui wawancara mendalam dan analisis dokumen terkait. Hasil penelitian menunjukkan bahwa peran Humas dalam perspektif Islam melibatkan komunikasi yang jujur, transparan, dan membangun kepercayaan dengan masyarakat. Humas bertindak sebagai jembatan antara institusi dan publik, mengedepankan nilai-nilai etika Islam dalam menyampaikan informasi. Di Badan Pengawas Pemilu Provinsi Jawa Barat, peran Humas membantu memastikan penyelenggaraan pemilu yang adil dan transparan sesuai dengan prinsip-prinsip Islam. Penelitian ini memberikan kontribusi dalam memahami bagaimana Islam dapat membentuk kerangka kerja konseptual bagi peran Humas dalam konteks pengawasan pemilu.